Powder Catalyst Fixation for Post‐Electrolysis Structural Characterization of NiFe Layered Double Hydroxide Based Oxygen Evolution Reaction Electrocatalysts. Issue 37 (11th August 2017) - Andronescu, Corina; Barwe, Stefan; Ventosa, Edgar; Masa, Justus; Vasile, Eugeniu; Konkena, Bharathi; Möller, Sandra; Schuhmann, Wolfgang
Abstract: Highly active electrocatalysts for the oxygen evolution (OER) reaction are in most cases powder nanomaterials, which undergo substantial changes upon applying the high potentials required for high‐current‐density oxygen evolution. Owing to the vigorous gas evolution, the durability under OER conditions is disappointingly low for most powder electrocatalysts as there are no strategies to securely fix powder catalysts onto electrode surfaces. Thus reliable studies of catalysts during or after the OER are often impaired. Herein, we propose the use of composites made from precursors of polybenzoxazines and organophilically modified NiFe layered double hydroxides (LDHs) to form a stable and highly conducting catalyst layer, which allows the study of the catalyst before and after electrocatalysis. Characterization of the material by XRD, SEM, and TEM before and after 100 h electrolysis in 5 m KOH at 60 °C and a current density of 200 mA cm −2 revealed previously not observed structural changes. Abstract : An active and stable OER catalyst was directly fixated on an electrode starting from a NiFe layered double hydroxide (LDH)/polybenzoxazine composite. Owing to its stable immobilization on the electrode, the catalyst can be characterized before and after electrolysis. After electrolysis at 200 mA cm −2 in 5 m KOH for 100 h, previously not reported structural changes were observed for the NiFe LDH.